SECONDARY MITOCHONDRIAL DYSFUNCTION IN ACUTE CORONARY SYNDROME - Y. A. Vasyuk; K. G. Kulikov; O. N. Kudryakov; O. V. Krikunova; I. A. Sadulaeva (Рациональная фармакотерапия в кардиологии)
So-called “metabolic” direction has been developing intensively during last decades. Its aim is the theoretical and practical analysis of the role of metabolic disorders in initiation and progression of many diseases. The pathogenic peculiarities of acute coronary syndrome (ACS) which result in developing of secondary mitochondrial dysfunction are considered as a subject of this review. The methods of laboratory diagnosis of mitochondrial dysfunction and possibilities of its pharmaceutical correction in patients with ACS are reviewed.